Filsafat Pesan - Teguh Ratmanto (Pusat Penerbitan Universitas (P2U) LPPM Unisba, 2006)
Message, in communication process, plays a significant role.In this case, message can be understood from two points of view, symbol (semiotics) and content (hermeneutics). Both, semiotics and hermeneutics, are in the domain of language, therefore the understanding of message requires the understanding of language as well. Either as system of grammar or social consensus, language should be understood of having great impact on how individual interpret message.